Factors influencing access to and utilisation of youth-friendly sexual and reproductive health services in sub-Saharan Africa: a systematic review - Ninsiima, Lesley Rose; Chiumia, Isabel Kazanga; Ndejjo, Rawlance (Reproductive health, 2021)
Despite the global agreements on adolescents' sexual and reproductive health and rights, access to and utilisation of these services among the youth/adolescents remain unsatisfactory in low- and middle-income countries which are a significant barrier to progress in this area. This review established factors influencing access and utilisation of youth-friendly sexual and reproductive health services (YFSRHS) among the youth in sub-Saharan Africa to inform programmatic interventions. A systematic review of studies published between January 2009 and April 2019 using PubMed, Web of Science, EMBASE, Medline, and Cochrane Library, and Google Scholar databases was conducted. Studies were screened based on the inclusion criteria of barriers and facilitators of implementation of YFSRHS, existing national policies on provision of YFSRHS, and youth's perspectives on these services. A total of 23,400 studies were identified through database search and additional 5 studies from other sources. After the full-text screening, 20 studies from 7 countries met the inclusion criteria and were included in the final review. Structural barriers were the negative attitude of health workers and their being unskilled and individual barriers included lack of knowledge among youth regarding YFSRHS. Facilitators of utilisation of the services were mostly structural in nature which included community outreaches, health education, and policy recommendations to improve implementation of the quality of health services and clinics for adolescents/youth to fit their needs and preferences. Stakeholder interventions focusing on implementing YFSRHS should aim at intensive training of health workers and put in place quality implementation standard guidelines in clinics to offer services according to youth's needs and preferences. In addition, educating the youth through community outreaches and health education programs for those in schools can facilitate utilisation and scale up of the service.